MEASURING STOCK RETURNS IN FINANCIAL RATIO PERSPECTIVE (Financial Study on Transportation and Logistics Sector Listed on Indonesia Stock Exchange) - Ai Nurhalimah; Dicky Jhoansyah; Asep Muhamad Ramdan (RADJA PUBLIKA, 2025)
This study examines how various financial metrics affect stock returns for logistics and transportation companies listed on the Indonesia Stock Exchange in 2023. The variables studied are Price Earnings Ratio (PER), Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA). Multiple linear regression and quantitative association techniques were used in this study. Purposive sampling was used to include a total of 34 eligible companies. According to this study, stock returns are affected by CR, DER, ROA, and PER simultaneously. As an added bonus, each financial indicator has a significant impact on each subsequent indicator. The findings of this study suggest that financial metrics can be helpful in evaluating stock returns, especially in the transportation and logistics industry.